2021
DOI: 10.1186/s12913-021-06846-x
|View full text |Cite
|
Sign up to set email alerts
|

Low and unequal use of outpatient health services in public primary health care facilities in southern Ethiopia: a facility-based cross-sectional study

Abstract: Background Outpatient department visits per individual for each year are one of the core indicators of healthcare delivery to assess accessibility or quality of services. In addition, this study aimed to assess health service utilisation and disease patterns in southern Ethiopia, by including the health authorities’ suggestions to improve the services. No study has assessed this in Ethiopia previously. Methods An institution-based cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The low performance in laboratory quality indicators has also been reported in other studies. For example, a study in Ethiopia also has reported that PHC facilities had inadequate access to essential laboratory tests; [32] and another study also in Ethiopia found that unavailability of laboratory tests in government owned health centres in southern Ethiopia affected outpatients service utilization causing most diagnoses to be based on clinical findings [33]. A study in four regions in Tanzania found that few dispensaries were providing diagnostic services for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The low performance in laboratory quality indicators has also been reported in other studies. For example, a study in Ethiopia also has reported that PHC facilities had inadequate access to essential laboratory tests; [32] and another study also in Ethiopia found that unavailability of laboratory tests in government owned health centres in southern Ethiopia affected outpatients service utilization causing most diagnoses to be based on clinical findings [33]. A study in four regions in Tanzania found that few dispensaries were providing diagnostic services for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, outpatient attendance per capita per year in urban areas ranged from 1.15 to 1.74. In contrast, outpatient attendance was lowest in pastoralist regions namely Afar (0.36) and Somali (0.21) [16,19].…”
Section: Study Settingmentioning
confidence: 99%
“…We selected the districts purposively since they were the study sites for the previous demographic study done by the same authors [33]. A total of 67,678 (92%) cases from 73,513 new cases had confirmed addresses [34]. The rest of the cases either didn't have an address or were from other districts.…”
Section: Study Participantsmentioning
confidence: 99%